Effects of Nicotine Gum Administration on Vision (ENIGMA-Vis): Study Protocol of a Double-Blind, Randomized, and Controlled Clinical Trial - Fernandes, Thiago P.; Hovis, Jeffery K.; Almeida, Natalia; Souto, Jandirlly J. S.; Bonifacio, Thiago Augusto; Rodrigues, Stephanye; Silva, Gabriella Medeiros; Andrade, Michael Oliveira; Silva, Jessica Bruna; Gomes, Giulliana H.; Oliveira, Milena Edite; Lima, Eveline Holanda; et al. (Frontiers in Human Neuroscience, 2020)
Studies reported that tobacco addiction was related to visual impairments, but one unresolved issue is whether the impairments are related to the many compounds existing in the cigarettes or to the effects of nicotine. On the other hand, nicotine gum can be used as replacement therapy or as a neuroprotective agent for some diseases. The main purpose of this controlled trial is to investigate the effects of nicotine gum on vision. The ENIGMA-Vis trial aims to compare two dosages of nicotine gum (2-mg and 4-mg) and a placebo gum in a randomized, double-blind, placebo-controlled trial of 100 participants to be allocated into a single group assignment of repeated measures (two studies; N= 50 for each one). Eligibility criteria are healthy nonsmokers not diagnosed with substance abuse and without an acute or chronic medical condition. Intervention will last three sessions for each participant with a window frame of one week per session. Study outcomes are (1) short-term effects of nicotine gum on contrast sensitivity; (2) short-term effects of nicotine gum on chromatic contrast discrimination; (3) whether demographics, body mass index, or serum cotinine predicts response of visual processing. This study addresses an important gap in the effects of nicotine on vision. One of the main takeaways of this study is to understand how the effects of nicotine on contrast sensitivity and chromatic contrast discrimination. This information will provide a further understanding of how nicotine interacts with early visual processes and help determine how the different components present during smoking can affect vision. Trial Registration number: RBR-46tjy3